Recommendations of the clinical target volume for the para-aortic region based on the patterns of lymph node metastasis in patients with biliary tract cancer - Long, Xin; Wu, Han; Yang, Lei; Xu, Hui; Dai, Jing; Wang, Wenbo; Xia, Ling; Peng, Jin; Zhou, Fuxiang (Frontiers in Oncology, 2022)
Background Even though the clinical target volume (CTV) in biliary tract cancer (BTC) patients has been proposed by several previous studies, the para aortic CTV for BTC is still not well-defined. The objective of this study was to determine the precise delineation of the para aortic CTV for BTC according to the distribution pattern and failure pattern of lymph nodes. Methods Computed tomography (CT)-, magnetic resonance imaging (MRI)- or positron emission tomography-computed tomography (PET-CT)-generated images of patients with BTC from 2015 to 2020 were analyzed retrospectively. The distribution patterns of lymph nodes in different regions were summarized. The diagnosed para aortic lymph nodes (PALNs) were manually mapped to standard axial CT images. The asymmetric CTV expansions from the para aortic were defined according to the distance from the volumetric centre of lymph node to the most proximal border of aorta. Results A total of 251 positive lymph nodes were found in the study cohort (n = 61 patients, 92 PALN). All PALNs were projected onto axial CT image of the standard patient. PALNs were concentrated in the 16a2 and 16b1 regions, and the involvement rates were 17% and 13% respectively. Therefore, the upper boundary of 16a2 and the lower boundary of 16b1 were defined as the cranial and caudal border of para aortic CTV, respectively. For the study cohort, the mean distance from the volume center of all lymph nodes in 16a2 and 16b1 to the proximal border of the aorta was 9 mm (range 4-24) in the front, 7 mm (range 3-14) on the left, and 12 mm (range 5-29) on the right. For the validation cohort (n=19 patients, 56 PALN), the mean distance from the center of the lymph node to the border of the aorta were both 10 mm on the left (range 5-20) and right (range 6-23). The mean distance in front of the aorta was 9 mm (range 5–23). Finally, a CTV expansion from the aorta of 18 mm in the front, 12 mm on the left, and 24 mm on the right resulted in 96% (73/76) coverage of PALNs in the study cohort. At the time of the validation, the described CTV could include 96% (47/49) of recurrent PALNs in the validation cohort. Conclusions The involvement rates of PALNs in 16a2 and 16b1 were the highest. Based on the distribution of PALNs, a new para-aortic CTV was defined to construct a more accurate target volume for adjuvant radiotherapy in BTC.